Adsorption of Ni(II) ions from waste water by δ-MnO2-MCM-41: isotherm, kinetics and thermodynamics. (2017) - Dash, Suresh Kumar
Δ-MnO2 modified MCM-41 adsorbent was prepared by loading different amounts of δ-MnO2 (5, 10, 15 and 20 weight %) onto MCM-41 by direct-synthesis method. The synthesised materials were characterised by powered XRD, scanning electron microscopy (SEM), Fourier transform infrared spectra (FTIR) and BET surface area. The adsorbent (δ-MnO2 -MCM-41) showed very high efficiency and sensitivity for removing Ni(II). By changing different parameters like initial Ni(II) concentration, pH of solution and temperature, it was concluded that highest adsorption took place for (5) δ-MnO2 -MCM-41 at 323 K and at a pH ~ 3.0. The equilibrium isotherms fitted well to Langmuir and Freundlich models explaining self-effacing adsorbate-adsorbent interactions. The kinetics of Ni(II) adsorption onto δ-MnO2 -MCM-41 followed pseudo-second-order rate and thermodynamic studies indicated endothermic nature with chemisorption mode.